Intellectual characteristics of Muslim personality and job characteristics as determinants for organizational citizenship behavior among Yemeni Secondary School Teachers - Kassim al-Amr, Fawzia; Nordin, Mohamad Sahari (2010)
The main finding of this study is that Islamic piety motivates schoolteachers to exceed the demands of their formal job description in the practice of their profession. The study also yielded an instrument to measure the degree to which a Muslim schoolteacher fits the description of a God-conscious person in carrying out his professional responsibilities. The objectives of the study was first to determine antecedents of Organizational Citizenship Behaviour (OCB) in the context of schools. Second the study aimed to construct-validate the multi-dimensionality of the organizational citizenship behavior. Drawing on earlier OCB studies, the proposed construct for School OCB has two dimensions, which are OCB towards individuals and OCB towards organization, and two groups of antecedents, which are job characteristics and personality characteristics. The job characteristics are grouped under two headings: Job Demand and Job Autonomy. For personality characteristics, the researcher chose to investigate what constitute indicators of the Moral Character of the Intellectual Muslim (MCIM) as given in the Qur’an, and found nine character traits that can be grouped under the rubrics of Interpersonal Characteristics, Self-Purification Characteristics and Endurance Characteristics. The results on data collected from 334 Yemeni secondary school teachers confirm the twofold dimensionality of School OCB. The measurement model for MCIM is also validated. The hypothesized construct for School OCB was tested through Structural Equation Modeling and the results show that Muslim personality characteristics do predict OCB, but job characteristics do not. There are several implications from the study that call for further research.